Jesus, Paul, and the people of God: a theological dialogue with N. T. Wright - Perrin, Nicholas; Hays, Richard B. (IVP Academic, 2011)
Pt. 1. Jesus and the people of God. Jesus and the victory of God meets the gospel of John / Marianne Meye Thompson -- N.T. Wright's response -- Knowing Jesus : story, history and the question of truth / Richard B. Hays -- N.T. Wright's response -- "Outside of a small circle of friends" : Jesus and the justice of God / Sylvia C. Keesmaat and Brian J. Walsh -- N.T. Wright's response -- Jesus' eschatology and kingdom ethics : ever the twain shall meet / Nicholas Perrin -- N.T. Wright's response -- Whence and whither historical Jesus studies in the life of the church? / N.T. Wright -- Pt. 2. Paul and the people of God. Glimpsing the glory : Paul's gospel, righteousness and the beautiful feet of N.T. Wright / Edith M. Humphrey -- N.T. Wright's response -- The shape of things to come? : Wright amidst emerging ecclesiologies / Jeremy S. Begbie -- N.T. Wright's response -- Did St. Paul go to heaven when he died? / Markus Bockmuehl -- N.T. Wright's response -- Wrighting the wrongs of the Reformation? : the state of the union with Christ in St. Paul and Protestant soteriology / Kevin J. Vanhoozer -- N.T. Wright's response -- Whence and whither Pauline studies in the life of the church? / N.T. Wright